PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ARTICULATE STORYLINE 3 PADA MATERI EFEK RUMAH KACA - Lia Ismi Oktaviani; Santa; Dita Destiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning media based on Articulate Storyline 3 is an interactive learning media used as a means of supporting teachers in delivering material in an interesting and easy-to-understand way for students through the use of text, images, videos, and animations. The use of this media is one of the innovations in the development of technology-based learning media. This study aims to develop learning media based on Articulate Storyline 3 on the Greenhouse Effect material using the Research and Development (R&D) method and the ADDIE model. The study was conducted at SDN Kedung Halang 1, Bogor City in grade IV involving one teacher and 40 students. The results of the study showed that the learning media developed was in the very suitable category for use, with a percentage of assessments from media experts of 88%, linguists 80%, lecturer material experts 87%, teacher material experts 80%, teacher responses 90%, and student responses 96.9%. Thus, learning media based on Articulate Storyline 3 is very suitable for use in the learning process.